Gambaran Hasil Pemeriksaan Penderita Demam Tifoid dengan Metode Widal di Laboratorium Kesehatan Daerah Kota Sukabumi - Zaranggi, Ahmad; Fauziah, Prima Nanda; Widhyasih, Retno Martini (Universitas Mohammad Husni Thamrin, 2024)
Typhoid fever is a systemic disease that becomes a world health problem. Typhoid fever occurs in both tropical and sub-tropical countries, especially in developing countries. To determine the exact diagnosis of this disease required examination Widal test. typhoid characterized by prolonged heat followedby bacteremia and bacterial invasion of Salmonella sp. The study aims to determine whether the diagnosis of Typhoid Fever Suspect isappropriate with the Widal Serology Test. The type of this research is descriptive research. Population of this research is outpatient in Sukabumi city health laboratory patients with typhoid fever in august 2020 – april 2021. The sample in this study were as many as 30 respondents. The results showed that the percentage of Widal Serology Test on positive Typhoid Fever was 18 people and 12 people with negative Widal Serology Test results. Positive results for Salmonella typhi O = 9 samples, Salmonella typhi H = 8 samples, Salmonella paratyphi AO as many as 9 samples, with positive results for Salmonella paratyphi BO as many as 11 samples, with positive results for Salmonella paratyphi CO as many as 13 samples, with positive results for Salmonella paratyphi AH as many as 7 samples, with a positive result of Salmonella paratyphi BH as many as 8 samples, with a positive result of Salmonella paratyphi CH as many as 7 samples. The conclusion of this study for the Widal Serology Test in positive Typhoid Fever was around 60%.The conclusion of the writing of this is more a hepatitis b patients (100%) men than women with age 30 - 65 years, decline and a rise in the number of platelets and SGPT and SGOT levels .